Indicators for resource recovery monitoring within the circular economy model implementation in the wastewater sector. (15th February 2022) - Preisner, Michał; Smol, Marzena; Horttanainen, Mika; Deviatkin, Ivan; Havukainen, Jouni; Klavins, Maris; Ozola-Davidane, Ruta; Kruopienė, Jolita; Szatkowska, Beata; Appels, Lise; Houtmeyers, Sofie; Roosalu, Kati
Abstract: The European Union is currently in the process of transformation toward a circular economy model in which different areas of activity should be integrated for more efficient management of raw materials and waste. The wastewater sector has a great potential in this regard and therefore is an important element of the transformation process to the circular economy model. The targets of the circular economy policy framework such as resource recovery are tightly connected with the wastewater treatment processes and sewage sludge management. With this in view, the present study aims to review existing indicators on resource recovery that can enable efficient monitoring of the sustainable and circular solutions implemented in the wastewater sector. Within the reviewed indicators, most of them were focused on technological aspects of resource recovery processes such as nutrient removal efficiency, sewage sludge processing methods and environmental aspects as the pollutant share in the sewage sludge or its ashes. Moreover, other wide-scope indicators such as the wastewater service coverage or the production of bio-based fertilizers and hydrochar within the wastewater sector were analyzed. The results were used for the development of recommendations for improving the resources recovery monitoring framework in the wastewater sector and a proposal of a circularity indicator for a wastewater treatment plant highlighting new challenges for further researches and wastewater professionals. Highlights: Circular Economy (CE) monitoring requires more indicators for resource recovery from wastewater. Recommendations for the design of accurate indicators were presented. Circularity indicators for wastewater treatment plants would improve CE monitoring framework. New challenges in adjusting CE indicators for the wastewater sector needs to be taken.